EVERYDAY MODERATORS AND HEALTH CORRELATES OF PHYSIOLOGICAL SYNCHRONY IN OLDER COUPLES - Pauly, T (Innov Aging, 2018)
Couples not only share their everyday lives but there is also evidence that they are physiologically ‘in sync’. This study aims to link everyday salivary cortisol synchrony to partner closeness and health biomarkers. We used multilevel modelling to analyze data from 85 older couples (aged 60–87 years) who completed questionnaires and provided saliva samples (cortisol) five times daily for 7 days. Cortisol levels were significantly correlated among partners. Higher daily perceptions of closeness with the partner were linked with increased cortisol synchrony in men but not women. Higher cortisol synchrony was associated with higher total and high-density lipoprotein cholesterol levels and steeper wake-evening cortisol slopes. Synchrony may be important for perspective-taking and empathy but could also put the partner at risk if physiological stress responses are frequently transmitted. More research is needed to examine the direction of transmission, and to analyse precursors and long-term consequences of physiological synchrony in couples.